2016
DOI: 10.1002/hlca.201500027
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Dimerization of Chlorophyll (a) and Its Hydrates: Implication for Chlorophyll (a) Aggregation

Abstract: Dimeric structures chlorophyll (a) (Chla) and their mono‐ and dihydrated have been suggested to play an important role in the mechanism of photoreaction center chlorophyll special pairs PSI and PSII. Despite their functional importance, the molecular basis structures for interacting two Chla molecules and the structural stabilization role of H2O in the formation of hydrated Chla dimer complexes is poorly understood. In this article, the different coordination modes between two interacting Chla molecules and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 69 publications
4
4
0
Order By: Relevance
“…It has been reported that the Mg–N bond can be elongated to 0.02–0.04 Å by neutral ligands [ 45 ]. In this work, the resulting distance order for all complexes was N1 > N3 > N2 > N4, in agreement with previous reports [ 48 , 49 , 50 ]. The Mg 2+ –AFB 1 complex caused small but noticeable changes in the geometry of the porphyrin moiety of chl a 1 due to a change in the coordination number (4 to 5) of the Mg 2+ ion.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…It has been reported that the Mg–N bond can be elongated to 0.02–0.04 Å by neutral ligands [ 45 ]. In this work, the resulting distance order for all complexes was N1 > N3 > N2 > N4, in agreement with previous reports [ 48 , 49 , 50 ]. The Mg 2+ –AFB 1 complex caused small but noticeable changes in the geometry of the porphyrin moiety of chl a 1 due to a change in the coordination number (4 to 5) of the Mg 2+ ion.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, in the higher-energy chl a 2 –AFB 1 complex, the Mg–N interatomic distances are longer than in uncoordinated chl a 2 ( Table 1 ) due to the saturated bond on the N1 ring, as previously reported (0.02 to 0.04 Å) [ 45 ]. In this work, the resulting distance order for all complexes was N1 > N3 > N2 > N4, in agreement with previous reports [ 48 , 49 , 50 ]. Additionally, the Mg 2+ –AFB 1 complex caused small but noticeable changes in the geometry of the porphyrin moiety of chl a 2 -α-D–AFB 1 , chl a 2 -α-E–AFB 1 , and chl a 2 -β-E–AFB 1 , which was due to a change in the coordination number (four to five) of the Mg 2+ ion.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations